2017
DOI: 10.1002/advs.201700296
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Effects of Gold Nanorods on Erythrocytes: Hemolysis and Hemoglobin Conformational and Functional Changes

Abstract: Gold nanorods (GNRs) are a unique class of metal nanostructures that have attractive potentials in biomedical applications, and the concern on their biological safety is concomitantly increasing. Hemocompatibility is extremely important as their contact with blood circulation is unavoidable during in vivo delivery. Herein, two kinds of GNRs coated with hexadecyltrimethylammonium bromide (C‐GNRs) or poly(sodium‐p‐styrenesulfonate) are used to test their potential toxicological effects in blood. C‐GNRs with posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…[36][37][38] Conformational Studies by CD and 3D Fluorescence Spectroscopy CD spectroscopy was applied to monitor the content of the secondary structure of the protein. 39 Figure 7A shows the CD spectra of BSA with the addition of metformin of a 1:25 molar ratio, which was in line with the molar ratio in drug preparation. The CD spectrum of native BSA showed two characteristic negative peaks at 208 nm and 222 nm.…”
Section: The Determination Of the Acting Force Between Metformin And Bsasupporting
confidence: 66%
“…[36][37][38] Conformational Studies by CD and 3D Fluorescence Spectroscopy CD spectroscopy was applied to monitor the content of the secondary structure of the protein. 39 Figure 7A shows the CD spectra of BSA with the addition of metformin of a 1:25 molar ratio, which was in line with the molar ratio in drug preparation. The CD spectrum of native BSA showed two characteristic negative peaks at 208 nm and 222 nm.…”
Section: The Determination Of the Acting Force Between Metformin And Bsasupporting
confidence: 66%
“…As negative values for enthalpy and entropy were observed during the binding process, this binding process is entropically opposed but enthalpically favoured within the temperature range. [20] Both the negative values for entropy and enthalpy of the binding process indicated that the interaction is dominated by van der Waals forces and hydrogen bonding in nature, and this phenomenon is in accordance with the fluorescence study. [21,22]…”
Section: Thermodynamic Measurements Of the Binding Processsupporting
confidence: 83%
“…It was reported that Ag + could react with 6-mercaptopurine to form highly fluorescent complexes under similar conditions (pH 7.2) [61]. Also the existing literature indicated that tryptophan could interact with gold nanorods and lead to enhancement in fluorescence intensity [62]. It was speculated that the increase in the fluorescence intensity was ascribed to highly fluorescent complexes generated in the reaction between high concentration of Ag + and CAT.…”
Section: Resultsmentioning
confidence: 99%